Modulation of the nuclearity of molecular Mg(ii)-phosphates: solid-state structural change involving coordinating solvents. Issue 24 (29th May 2019) - Santra, Biswajit; Narayanan, Ramakirushnan Suriya; Kalita, Pankaj; Kumar, Vierandra; Mandal, Debdeep; Gupta, Vivek; Zimmer, Michael; Huch, Volker; Chandrasekhar, Vadapalli; Scheschkewitz, David; Schulzke, Carola; Jana, Anukul
Abstract : The syntheses of mono-, di-, tetra-, hexa-, and polynuclear Mg(ii )-phosphate monoesters are reported. Abstract : Herein, we report the synthesis and molecular structures of various magnesium(ii )-phosphate monoesters. By using a bulky aryl substituted phosphate monoester, ArOPO3 H2 (Ar = 2, 6-(CHPh2 )2 -4- t Bu-C6 H2 ), we have reproducibly assembled mono-, di-, tetra- (cage and ring), hexa-, and polynuclear magnesium(ii )-phosphate monoesters. Interestingly, the hexanuclear magnesium(ii )-phosphate monoester encapsulates an open-cage dodecanuclear water cluster.